GAMBARAN PSIKOSOSIAL ANAK JALANAN USIA REMAJA - Erna Marni (Jurnal Keperawatan Abdurrab, 2020)
Adolescence is a period of self-actualization which includes physical, emotional, intellectual and social changes that will affect the development process of an individual . At this time individuals especially street children are at risk of experiencing behavioral disorders, delinquency and occurrence of violence, both as victims or as perpetrators of violence . This condition tends to make street children behave negatively and not obey with the rules. In addition, street children are also very vulnerable to crime and violence and even sexual exploitation such as a sexual harassment, abuse, becoming victims of human trafficking and even objects for pornography . In this situation will certainly cause psychosocial problems that will affect the relations with the environment in their life. This research aims to see the psychosocial description of street children, especially at adolescents. The type of this research is a simple description with 38 street children's in Pekanbaru City as a respondents. The results showed that most street children (55.3%) have a positive psychosocial, It is expected that Social Service Unit in Pekanbaru will provide skills training to street children as to increase the positive psychosocial aspects of street children.